2014
DOI: 10.1093/ndt/gfu196
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of Akt signaling in chronic kidney disease

Abstract: Renal fibrosis, particularly tubulointerstitial fibrosis, is the common final outcome of almost all chronic kidney diseases. However, the mechanisms involved in the development of renal fibrosis are poorly understood. The Akt (also known as protein kinase B, PKB) family is serine/threonine protein kinases that play critical roles in regulating growth, proliferation, survival, metabolism and other cellular activities. Cytokines, high-glucose medium, transforming growth factor-β1 or advanced glycation end-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 128 publications
6
61
2
Order By: Relevance
“…Previous studies suggest that Akt regulates transcriptional activity of NFκB by inducing phosphorylation and subsequent degradation of IκB [28,29]. In this study, we applied Akt inhibitor triciribine [30], and found that Akt inhibition decreased ADR-induced nuclear translocation of NFκB and cellular apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies suggest that Akt regulates transcriptional activity of NFκB by inducing phosphorylation and subsequent degradation of IκB [28,29]. In this study, we applied Akt inhibitor triciribine [30], and found that Akt inhibition decreased ADR-induced nuclear translocation of NFκB and cellular apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…However, downregulation of nephrin, podocin, and CD2AP by activated AKT in morphine treated mice is a contradiction to the evidence that nephrin, podocin, and CD2AP themselves activate AKT via activation of PI3K to promote survival of podocytes [165]. It is pertinent to note that PI3K/AKT signaling can contribute to hypertrophy of mesangial cells upon activation by TGF- β 1 [166], whereas podocytes may also undergo hypertrophic change in response to high glucose, intraglomerular pressure, and Ang II (Figure 3) [167]. Although ROS can activate PI3K/AKT signaling pathway by inducing AKT phosphorylation [54, 168], they can also be accountable for inactivation of AKT by its diminished phosphorylation [103, 169, 170].…”
Section: Mechanisms Of Ros-mediated Glomerular Renal Injury In Diamentioning
confidence: 99%
“…Tight regulation between TG synthesis, hydrolysis, secretion and fatty acid oxidation is required to prevent lipid accumulation and/or depletion from cells (Mantzaris et al, 2011). Activation of AMP-activated protein kinase (AMPK) and AKT (also known as protein kinase B, PKB) regulates lipid metabolism by stimulating fatty acid uptake and promoting energy use by increasing total cellular ATP content via glycolysis and oxidative phosphorylation control (Bellacosa et al, 1991;Lan and Du, 2015). In addition, AMPK stimulation has been reported to restore lipid metabolism disorder in ob/ob mice (Samovski et al, 2015;Zeng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%